Field surveys of natural populations of Begonia L. in Thailand - Phutthai, Thamarat; Sands, Martin; Sridith, Kitichate (Thai Forest Bulletin (Botany), 2014)
Field surveys of natural populations of the genus Begonia L. (Begoniaceae) were undertaken in all floristic regions of Thailand from June 2007 to May 2008. Among the currently recognized species 30 were collected from various habitats on a range of substrata; terrestrial, epiphytic and lithophytic. Natural populations of all Thai begonias occur only near streams or waterfalls or in other humid places, such as moist bark or rocks, from near sea-level in eastern and peninsular Thailand to mountain summits over 2,000 m in the North of the country. Based on taxon abundance and distribution, the begonias collected fall roughly into three regional groups, namely Northern, Central and Peninsular species. Only one species, Begonia integrifolia Dalzell, is found in many parts of the country and another two, Begonia sinuata Wall. ex Meisn. var. sinuata and B. variabilis Ridl., occur in two of the above regional groups, being found in both the Southeastern and Peninsular floristic regions. All other taxa collected were recorded from only one floristic region of Thailand.